PERAN PUSTAKAWAN DALAM PENELUSURAN INFORMASI DI PERPUSTAKAAN UNIVERSITAS BINA DARMA PALEMBANG - Wati , Oka Widia (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
Searching for information is one of the main services provided by the university library, functioning to support various academic activities carried out by students and lecturers. In this context, librarians play a very important role, especially in helping library users to find, evaluate, and utilize information sources that are relevant to their needs. This research aims to analyze in depth the role of librarians in the process of searching for information at the Bina Darma University Library, Palembang. Using a qualitative approach, this research explains several key aspects, namely the definition of a librarian, librarian competencies, and the role of librarians in searching for information. The research results show that librarians have a crucial role in increasing information literacy among students and lecturers, as well as ensuring efficient and effective access to various available library resources.